Multiple Plant Growth-Promotion Traits in Endophytic Bacteria Retrieved in the Vegetative Stage From Passionflower - Cueva-Yesquén, Luis Gabriel; Goulart, Marcela Cristina; Attili de Angelis, Derlene; Nopper Alves, Marcos; Fantinatti-Garboggini, Fabiana (Frontiers in Plant Science, 2021)
Bacteria exhibiting beneficial traits like increasing the bioavailability of essential nutrients and modulate hormone levels in plants are known as plant growth promoting (PGP) bacteria. The occurrence of this specific group of bacteria in the endophytic environment may reflect the decisive role they play in a particular condition. This study aimed to determine the taxonomical diversity of the culturable bacterial endophytes, isolated in the vegetative stage of passionflower (Passiflora incarnata) and assess its potential to promote plant growth by phenotypic and genotypic approaches. The sequencing and phylogenetic analysis of the 16S rRNA gene allowed us to classify 58 bacterial endophytes into nine genera. Bacillus (70.7%) was the most dominant genus, followed by Pseudomonas (8.6%) and Pantoea (6.9%). A few isolates belonged to Rhodococcus and Paenibacillus, whereas the genera Lysinibacillus, Microvirga, Xanthomonas, and Leclercia were represented by only one isolate. The strains were tested for nitrogen fixation, phosphate solubilization, indole acetic acid synthesis and siderophore production. Moreover, PGP related genes (nifH, ipdC, asb, AcPho) were detected by PCR-based screening. Most of the isolates (94.8%) displayed potential for at least one of the PGP traits tested by biochemical assays or PCR-based screening. Nine strains were selected based on results from both approaches and were evaluated for boosting the Cape gooseberry (Physalis peruviana) germination and growth. All tested isolates improved germination in vitro, and the majority (78%) increased growth parameters in vivo. The results suggested that most of culturable bacteria inhabiting P. incarnata in the vegetative stage could be used as probiotics for agricultural systems. Besides, their occurrence may be associated with specific physiological needs typical of this development stage.